Scorching heat and shrinking horizons: The impact of rising temperatures on marriages and migration in rural India - Manisha Mukherjee; Bruno Martorano; Melissa Siegel (United Nations University (UNU), Maastricht Economic and Social Research Institute on Innovation and Technology (UNU-MERIT), 2024)
This study delves into the gendered impacts of rising temperatures from climate change on long-term female migration patterns in rural India. We utilize a panel fixed-effects model to investigate the relationship between temperature levels and migration trends by employing a district-level panel dataset that combines Census data for years 1991, 2001, and 2011, multiple rounds of household surveys, and local weather measurements. Our results showcase statistically significant declining effects of rising temperatures on female rural-rural and rural-urban migration in the country. Specifically, the findings suggest that a 1 degree Celsius temperature increase is associated with a 22% decline in rural-urban and a 13% decline in rural-rural female migration in an average district in India. This decline is primarily due to diminishing marriage-related migration among women in the northern districts of the country, which have a historically high prevalence of dowry. We identify decreasing agricultural yields from rising temperatures as an underlying mechanism that is reducing resources to finance dowry in northern India. We further note that the declines in female migration are driven by districts with poor access to credit, and more so in the northern districts.
Keywords: J12; O15; Q54; 330; Climate change; Migration; Marriages; Dowry; India